The Effectiveness of Aerobic and Anaerobic Methods During Start-up in Biological Shrimp Pond Wastewater Treatment - Sanjaya, Eli Hendrik; Amara, Aulia; Hengky Pamungkas, Yahya; Ricky Wijaya, Anugrah; Santoso, Aman; Yulistyorini, Anie; Li, Yu-You; Chen, Hong; Fadhil Md Din, Mohd (Chemistry Department, The University of Brawijaya, 2023)
One of the aquaculture wastes is shrimp pond wastewater (SPW). Generally, SPW comes from the rest of shrimp feed, shrimp dung, and died shrimp during the cultivation. As SPW is organic waste, biological wastewater treatment is the best choice. Biological method has low operating costs and environmentally friendly. There are two kind of biological methods, namely aerobic and anaerobic. Both methods have advantages and disadvantages. In this research, the performance of aerobic and anaerobic methods in treating SPW were investigated using batch experiment for more than 200 days. The results showed that the performance of the aerobic system in the initial phase was better than that of the anaerobic system, especially, in phase one which is the adaptation phase. In the first phase, COD, carbohydrate and protein removal in the aerobic system were 25.93%, 75.2% and 88.59%, while in the anaerobic system were 12.82%, 36.03% and 51.01%. In phases 5 to 10, both systems have similar performance with the optimum performance in phase 9 with 6 times substrate dilution. In this optimum phase, the COD removal values are 90% and 85% for aerobic and anaerobic systems, respectively. Meanwhile, the removal of carbohydrates and protein from both systems is about 95%.